Mutual Fund & Foreign Institutional Investors : Pre & Post Crisis Dynamics - De, Suddhasanta; Ghosh, Keya Das (Indian Journal of Research in Capital Markets, 2019)
Institutional investors are smart traders and their informational advantage about firm values may propel them to play a significant role in price discovery. The trust of the market on institutional trade may also induce herding leading to faster price correction or even deviation due to overreaction. Foreign institutional investors (FII) may often score over domestic mutual funds (MF) in efficient trading decisions due to perceived superiority in analytical skills and investment experience. Researchers contradicting such views cited familiarity of the local environment and absence of linguistic or cultural barriers for domestic mutual funds as the reason of their superiority in security valuation, market timing, and trade decision. This paper was an attempt to find an answer to a controversial question about who is better informed about firm values, FIIs or the domestic mutual funds.